Insights into portuguese stock market efficiency using DEA - Ferreira, N. B. (The European Proceedings of Social and Behavioural Sciences, 2016)
US subprime crisis and the European sovereign debt crisis affected indiscriminately both the economic and the financial sectors giving rise to a bank run which made the survival of many other banks became uncertain, and by contagion the equity markets tumbled. In this context, this study runs a Data Envelopment Analysis model to analyse individual market return and net sales in light of the interest income, depreciation, cost of goods and employees. Using data from the largest companies of the Portuguese index stock market, the results showed that energy, communications and banking are the sectors more prevalent regarding revenue efficiency.